“Early Exposure” Course and Its Affect in Post-graduate Students’ Teaching Ability - Christian Anggraini; Lailatul Musyarofah; Kani Sulam Taufik (Budapest International Research and Critics University, 2022)
The purpose of this study was to ascertain the post-graduate students at STKIP PGRI Sidoarjo’s perceptions of the Early Exposure (EE) Subject for the academic year 2021/2022. The subjects of this descriptive qualitative method study were 20 students from Batch 7 of the Master of English Education (MPBI) program at STKIP PGRI Sidoarjo in the academic year 2020/2021, who were in their third semester at the time of the research. As the research instruments, the adapted questionnaire and the open-ended interview were used. The total mean result showed that the mean score of each statement was classified as Agree (A) or Strongly Agree (SA). The total mean showed 3.78 (94.8%). As a result, the post-graduate students’ perception of the EE subject was classified as Strongly Agree (SA) on an interval scale and was positive attitude. It also demonstrated that the post-graduate students at STKIP PGRI Sidoarjo were enthusiastic about the EE subject and had improved their teaching abilities. The post-graduate students who completed the EE subject confirmed that it was a positive experience that helped them improve their teaching abilities consent to take part in teaching practice at the university level, and they expressed gratitude for the opportunity. As a result, they place a high value on the role of the EE subject in their academic achievement.